Monopod robot prototype with reaction wheel for hopping and posture stabilisation. (18th January 2022) - Anzai, Asahi; Doi, Toshihide; Hashida, Kazuki; Chen, Xuechao; Han, Lianqiang; Hashimoto, Kenji
The purpose of this study is to develop a one-legged hopping robot, which has the fewest number of legs as a legged robot, and to realise hopping motion, upright posture stabilisation and getting up. The long-term goal is to develop biped robots and multi-legged robots capable of jumping and running. We designed and fabricated an electrically driven 2-DoF monopod MH-1 with pitch axes at the hip and knee joints equipped with a reaction wheel. MH-1 realised hopping while the robot is constrained so that it could only move in the vertical direction. We also proposed a control method for upright posture stabilisation and getting up of a monopod robot using a reaction wheel. MH-1 realised getting up and stabilising its upright posture within the range of the motor characteristics.